2012
DOI: 10.5194/acp-12-10613-2012
|View full text |Cite
|
Sign up to set email alerts
|

Future air quality in Europe: a multi-model assessment of projected exposure to ozone

Abstract: Abstract. In order to explore future air quality in Europe at the 2030 horizon, two emission scenarios developed in the framework of the Global Energy Assessment including varying assumptions on climate and energy access policies are investigated with an ensemble of six regional and global atmospheric chemistry transport models.A specific focus is given in the paper to the assessment of uncertainties and robustness of the projected changes in air quality. The present work relies on an ensemble of chemistry tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 47 publications
(50 reference statements)
3
76
1
2
Order By: Relevance
“…At the continental scale the efficiency of emission reductions was demonstrated but models provided a large spread of responses in city centres. The ability of an ensemble of six chemistry transport models to capture recent observed ozone trends was also discussed by Colette et al (2012). They found that models efficiently captured the increase in NO x -saturated areas, such as the Benelux region and the decrease in NO x -limited areas (many rural regions in Europe).…”
Section: Challenges In Modelling Ozonementioning
confidence: 99%
See 2 more Smart Citations
“…At the continental scale the efficiency of emission reductions was demonstrated but models provided a large spread of responses in city centres. The ability of an ensemble of six chemistry transport models to capture recent observed ozone trends was also discussed by Colette et al (2012). They found that models efficiently captured the increase in NO x -saturated areas, such as the Benelux region and the decrease in NO x -limited areas (many rural regions in Europe).…”
Section: Challenges In Modelling Ozonementioning
confidence: 99%
“…but an additional co-benefit of at least 40 % (depending on the indicator) was attributed to the climate policy (Colette et al, 2012). A study by Crawford-Brown et al (2012) focused on the co-benefits to O 3 -and PM-related health effects resulting from implementation of climate policy in Mexico.…”
Section: The Future -Air Quality and Climatementioning
confidence: 99%
See 1 more Smart Citation
“…For ozone the lateral boundary concentrations are based on ozone climatology scaled by measurements from the clean sector at Mace Head, Ireland, unaffected by European emissions. A detailed description of the model can be found in Simpson et al (2012) Colette et al, 2011Colette et al, , 2012Angelbratt et al, 2011).…”
Section: Emep Model Runs -Model Setupmentioning
confidence: 99%
“…With the exception of ship emissions in the Baltic Sea and the North Sea the emissions of air pollutants are based on the EC4MACS Interim Assessment of "Greenhouse gases and air pollutants in the European Union: baseline projections up to 2030" (Amann et al, 2012). The emissions include both land-based emissions and emissions from international shipping.…”
Section: Present and Future Emissionsmentioning
confidence: 99%